Prototype design collection : series 3 / Ahmad Najmie Rusli - Rusli, Ahmad Najmie (School of Mechanical Engineering, 2025)
This digital book on Prototype Design Collection Series 3 (PDC Series 3) is published as a reference design for mechanical engineering students. The designs presented experience a few phases of analysis before fabrication of prototype. Each project summarizes the project description, prototype, figures, and design parameter. The design products vary in tools or equipment for household, workshop, entrepreneur, etc. Suggested material and detail of prototype dimension are also mentioned in this book. It is hoped that this book will assist the students to have more ideas on innovation design products in the future.